Fetal cardiac services during the COVID-19 pandemic: how does it affect parental counseling? - Kovacevic, Alexander; Bär, Stefan; Starystach, Sebastian; Elsässer, Michael; Locht, Thomas van der; Mohammadi Motlagh, Aida; Ostermayer, Eva; Oberhoffer-Fritz, Renate; Ewert, Peter; Gorenflo, Matthias; Wacker-Gußmann, Annette (Journal of Clinical Medicine, 2021)
The COVID-19 pandemic impacts health care providers in multiple ways, even specialties that do not seem to be affected primarily, such as fetal cardiac services. We aimed to assess the effects on parental counseling for fetal congenital heart disease (CHD). In this multicenter study, we used a validated questionnaire. Parents were recruited from four national tertiary medical care centers (n = 226); n = 169 had been counseled before and n = 57 during the pandemic. Overall counseling success including its dimensions did not differ between the two groups (p = n.s.). However, by applying the sorrow scale, we could demonstrate that parents counseled during the pandemic were significantly more concerned (p = 0.025) and unsure (p = 0.044) about their child’s diagnosis, therapy and outcome. Furthermore, parents expressed a significantly increased need for written and/or online information on fetal heart disease (p = 0.034). Other modifiers did not affect counseling success (p = n.s.). We demonstrate that the COVID-19 pandemic impacts effectiveness of parental counseling for fetal CHD, possibly by altering parental perceptions. This needs to be taken into consideration when counseling. Implementing alternative and innovative approaches (e.g., online conference or virtual reality tools) may aid in facilitating high-quality services in critical times such as in the present pandemic.
Gesehen am 02.08.2021